IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DI SD ISLAM TERPADU ANNIDA SOKARAJA KABUPATEN BANYUMAS TAHUN 2018-2019 - Tanwirotul Fadlilah, Lilik (CV. Amerta Media, 2019)
Islamic Education in general can be understood as an effort to increase the faith, understanding, endurance and practice of students about Islam so that it becomes a Muslim person who has faith and piety and a noble character in personal life, community, nation and state. The general purpose of this study was to find out the implementation of Islamic Education at the Integrated Islamic Elementary School of Annida Sokaraja. There are three research questions that are proposed as a research problem in this study. These questions cover the problem about: the learning process of Islamic Education, the inhibiting factors and supporting learning process and the success of PAI at Annida Sokaraja Integrated Islamic Elementary School. Based on the discussion of the results in this study, it was obtained a description that in general the process of implementing Islamic Religious Education at SD IT Annida Sokaraja could be said to be successful. This is evidenced by the achievement of school goals and student achievement, both in the form of achievement of the KKM PAI and KKM values of the foundation programKey Words: implementation, Islamic education